Design and Shear Bearing Capacity Calculation of All-Welded Irregular Joints in Steel Traditional Chinese Buildings - Zhanjing Wu; Xinwu Wang; Xin Bu; Jinshuang Dong (Buildings)
Steel traditional Chinese buildings (STCBs) are constructed using modern materials, replicating the esthetics of ancient Chinese buildings, but their irregular joints differ significantly from those in conventional steel structures. To investigate the influence of beam section shape and axial compression ratio on the failure mode and shear resistance of all-welded irregular joints (WIJs) in STCBs, the size proportion relationships in the traditional Chinese modular construction system for such joints in existing practical projects are analyzed. Four exterior joint specimens were designed and fabricated for pseudo-static loading tests. The failure mode, hysteresis curve, and skeleton curve of the specimens were obtained. The test results indicate that the failure mode of the specimens involves shear deformation in the lower core area, with final failure due to crack formation in the weld at the junction between the column wall and the beam flange. As the axial compression ratio increases, the bearing capacity of the joint decreases. Based on the test results, the numerical model was established by using finite element software Abaqus2016, and parameter analysis was performed by varying the axial compression ratio of the column. After analyzing the force transfer mechanism of the core area in the WIJs of STCBs, a simplified calculation formula for the shear bearing capacity of the core area was derived based on the proportional relationship outlined in the construction manual from the Song Dynasty. The calculated results show good agreement with the experimental results, providing a basis for the structural design of WIJs in STCBs.